Learning Management System Innovation for Employee Competency Development - Marsono, Marsono; Yohanitas, Witra Apdhi; Manorsa, Ferdinand; Firmasyah, Nurhuda; Ardiansyah, Fahri (KnE Social Sciences, 2022)
In the era of digital technology, it is easy to find information in order to develop ASN self-competence. Classical training and learning have begun to shift towards digital forms to meet the demands of the COVID-19 pandemic. However, digital learning will make government agencies compete to create their own systems but may cause inefficiencies. The integration of a learning management system is important to implement. In 2021, LAN developed a learning management system that can facilitate and integrate existing systems. This system is an innovative new LAN method to develop ASN competence in a digital learning platform called Multitenance ASN Unggul. This research aimed to examine how to realize and manage this Multi-tenance ASN Unggul platform, and the progress of its system development. Qualitative methods were used. It was found that this platform can facilitate ASN learning through micro-learning; it allows training institutions to create and integrate learning management systems; and it facilitates access for ASN because it is equipped with single sign on (SSO) technology. In conclusion, several challenges remain in the implementation of this innovation, such as that there are already so many diverse LMS systems, there is still a silo effect from government training institutions, there is a misperception of the concept of integration in ASN, and there are concerns about attribution in training implementation. For this reason, it is necessary to carry out further socialization in government training institutions. This system will increase the effectiveness and efficiency of the ASN competency development process in the future. Keywords: training and learning, Multitenance ASN Unggul, LAN innovation, competence development